2013
DOI: 10.1145/2438645.2438650
|View full text |Cite
|
Sign up to set email alerts
|

Speed Scaling with an Arbitrary Power Function

Abstract: "What matters most to the computer designers at Google is not speed, but power, low power, because data centers can consume as much electricity as a city." -Dr. Eric Schmidt, CEO of Google [12]. AbstractAll of the theoretical speed scaling research to date has assumed that the power function, which expresses the power consumption P as a function of the processor speed s, is of the form P = s α , where α > 1 is some constant. Motivated in part by technological advances, we initiate a study of speed scaling with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…To the best of our knowledge there is no other algorithmic work directly related to the results in this paper. [4] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and weighted fractional delay. [4], [5] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and total (unweighted) (integer) delay.…”
Section: Related Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge there is no other algorithmic work directly related to the results in this paper. [4] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and weighted fractional delay. [4], [5] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and total (unweighted) (integer) delay.…”
Section: Related Resultsmentioning
confidence: 99%
“…[4] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and weighted fractional delay. [4], [5] showed that a natural online algorithm is 2-competitive for the objective of a linear combination of energy and total (unweighted) (integer) delay. Previously, [3], [6], [7], [8], [9], [10], [11] gave online algorithms with competitive analyses in the case that the power function was of the form s α .…”
Section: Related Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on this metric suggest that the optimal dynamic speed scaling function should be a function of n, the number of jobs in the system. Later, Bansal, Chan and Pruhs [8] showed that SRPT with the speed scaling function P −1 (n+1) is 3-competitive for an arbitrary power function P . Andrew, Lin and Wierman [10] show that SRPT with speed scaling function P −1 (nβ) is 2-competitive, and is optimal among the class of "natural" speed scaling functions.…”
Section: B Speed Scaling Systemsmentioning
confidence: 99%
“…This work pre-dated the widely-cited Yao, Demers, and Shenker (YDS) paper [3] on speed scaling in 1995, which provided the first formal treatment of the speed scaling problem, including several heuristic algorithms, as well as proofs that they were within a constant factor of optimal. The latter paper triggered substantial follow-on work by Albers [4], [5], Bansal [6], [7], [8], and others on improved algorithms, tighter bounds, and alternative metrics for evaluating speed scaling designs.…”
Section: Introductionmentioning
confidence: 99%